2020
DOI: 10.1038/s41467-020-20192-2
|View full text |Cite|
|
Sign up to set email alerts
|

Consistent effects of pesticides on community structure and ecosystem function in freshwater systems

Abstract: Predicting ecological effects of contaminants remains challenging because of the sheer number of chemicals and their ambiguous role in biodiversity-ecosystem function relationships. We evaluate responses of experimental pond ecosystems to standardized concentrations of 12 pesticides, nested in four pesticide classes and two pesticide types. We show consistent effects of herbicides and insecticides on ecosystem function, and slightly less consistent effects on community composition. Effects of pesticides on eco… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
58
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 74 publications
(63 citation statements)
references
References 40 publications
(18 reference statements)
1
58
0
Order By: Relevance
“…With a global annual application of pesticides exceeding 4.1 million tons (FAO 2020), their occurrence in surface and ground waters is increasingly reported (Wittmer et al 2010, Ippolito et al 2015, Stehle and Schulz 2015, in addition to the recurrent presence of other agrochemicals such as fertilizers (V€ or€ osmarty et al 2010). Despite these global trends, there are a limited number of studies addressing how the rising load and diversity of synthetic agrochemicals entering freshwaters affect the ecological functioning of communities and ecosystems (Gessner and Tlili 2016, Mazor et al 2018, Reid et al 2019; but see Rumschlag et al 2020).…”
Section: Introductionmentioning
confidence: 99%
“…With a global annual application of pesticides exceeding 4.1 million tons (FAO 2020), their occurrence in surface and ground waters is increasingly reported (Wittmer et al 2010, Ippolito et al 2015, Stehle and Schulz 2015, in addition to the recurrent presence of other agrochemicals such as fertilizers (V€ or€ osmarty et al 2010). Despite these global trends, there are a limited number of studies addressing how the rising load and diversity of synthetic agrochemicals entering freshwaters affect the ecological functioning of communities and ecosystems (Gessner and Tlili 2016, Mazor et al 2018, Reid et al 2019; but see Rumschlag et al 2020).…”
Section: Introductionmentioning
confidence: 99%
“…While such experiments are crucial to improve ecological risk assessment of pesticides and the mechanistic understanding of their specific modes of action and detrimental effects, they often overlook the possibility that populations can evolve resistance to applied toxicants (e.g. using ‘naïve’ pooled populations and communities of zooplankton, Rumschlag et al, 2020 ). Evolved pesticide resistance in natural populations of Daphnia in response to agricultural pesticide application was shown both across spatial gradients (organophosphates: Bendis & Relyea, 2014 ; carbamates: Coors et al, 2009 ; Jansen et al, 2015 ) as well as in response to historical contamination (resurrection ecology, organophosphates: Simpson et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, predicting the effects of pesticides could be simplified if organisms that are taxonomically related or share similar functional roles within an ecosystem have similarities in their responses to pesticides, a trend that has been shown in previous toxicological research (Hua & Relyea, 2014;Ippolito et al, 2012;van den Berg et al, 2021). For example, our previous research has shown consistency in the effects of pesticides by class and type on parasite transmission, ecosystem functions, and macroinvertebrate and amphibian communities (Rumschlag et al, 2019(Rumschlag et al, , 2020. In addition, organisms that share functional roles in a community have been shown to respond similarly to types and classes of pesticides (Rumschlag et al, 2020).…”
Section: Introductionmentioning
confidence: 98%